PPAR-γ and GLUT-4 Mediated Insulin Sensitizing Action of Paspalum scrobiculatum Grains; An In vivo and In silico Study towards Validating it as a Long-Term Therapy for Type 2 Diabetes - Gangavaram, Jyothi Reddy; Latha, Gourelly; Pooja, Mangari; Nithya, Somanjeri; Rajasekhar, Allagadda; Reddy, Kesavan Bhaskar (Indian Journal of Pharmaceutical Education and Research, 2026)
Purpose: Insulin Resistance (IR) usually results from a decline in levels of critical signalling proteins, their functional modifications, or both. Food and drinks rich in fat, energy and/or sugars increases the risk of obesity, promoting systemic IR and Type 2 Diabetes (T2D). Therapeutic approaches using natural compounds which promote and upregulate Glucose Transporter-4 (GLUT-4) and/or Peroxisome Proliferator Activated Receptors-y (PPAR-y), or increase adiponectin productions are advocated in treating T2D. The present study aimed to evaluate in vivo and in silico insulin sensitizing effect of P. scrobiculatum grains and to analyse the phytochemical composition using GC-MS technique. Materials and Methods: Sprague-Dawley rats were induced with IR by utilizing High Fructose and High Fat (HFHF) feed for 10 weeks. These rats were treated with fractions of P. scrobiculatum and pioglitazone for 6 weeks. Biochemical parameters, mRNA levels of PPAR-y in adipose tissue and GLUT-4 in skeletal muscle were assessed. Further, GC-MS analysis of P. scrobiculatum followed by in silico screening towards GLUT-4 and PPAR-y was performed. Results: Treatment with P. scrobiculatum significantly reduced Blood Glucose levels and normalized serum insulin, lipid and adiponectin levels. GLUT-4 and PPAR-y mRNA levels appeared to be markedly elevated in the groups treated with Pioglitazone and P. scrobiculatum. GC-MS analysis of P. scrobiculatum revealed the presence of different constituents which were subjected to docking studies. This indicated 9,12-Octadecadienoic acid methyl ester and 9,17-Octadecadienal (Z)-showing good binding affinity towards PPAR-y and GLUT-4. Conclusion: The present in vivo and in silico studies demonstrated insulin sensitizing action of P. scrobiculatum grains mediated by GLUT-4, PPAR-y and adiponectin, thus concluding the multifaceted benefits in long-term treatment of T2D.
Keywords: Glucose transporter-4; High fructose High Fat feed; Insulin resistance; Paspalum scrobiculatum; PPAR-γ; Type 2 Diabetes.